Non-invasive monitoring of stress in wild Asian elephants (Elephas maximus) in Peninsular Malaysia - Wong, E.P. (2018)
Translocation of wild Asian elephants (Elephas maximus) is used extensively to mitigate human-elephant conflict (HEC) in Peninsular Malaysia since 1974. Very little is known about the fate of translocated elephants after relocation due to challenges in observing elephants in the dense rainforest. Advances in wildlife endocrinology suggest that faecal glucocorticoid metabolites (fGCM) can be used to study adrenal activity remotely, to assess the Hypothalamic-Pituitary-Adrenal (HPA) axis response towards stressors.